INFLUENCE OF 20-YEAR REDUCTION IN DOOR-TO-BALLOON TIMES ON OUTCOMES OF PATIENTS WITH ANTERIOR ST-ELEVATION MYOCARDIAL INFARCTION UNDERGOING PRIMARY PERCUTANEOUS CORONARY INTERVENTION: A PROSPECTIVE COHORT STUDY. - Kumar, Vikas (Student's Journal of Health Research Africa, 2024)
Background The study aims to investigate the relationship between shortened DTB times and long-term clinical outcomes in ST-Elevation Myocardial Infraction (STEMI) patients receiving Primary Percutaneous Coronary Intervention (PPCI). Methods This 20-year study at the tertiary care center examined how reduced door-to-balloon timings (DBT) affected outcomes for anterior STEMI patients from 2003 to 2022. The study examined 829 anterior STEMI patients who received PPCI within 12 hours of presentation. Patient data were divided into four five-year quartiles (2003-2007, 2008-2012, 2013-2017, and 2018-2022). Analyses included demographic, clinical, and mortality data. Age, hypertension, smoking status, obesity, hospital stay, diabetes, and DBT were important. The multivariate analysis accounted for gender, age, comorbidities, clinical shock, ejection fraction, and mitral regurgitation. Results The study found a substantial drop in patient age (63.4 to 60 yrs, p<0.01), with hypertension, smoking, and obesity prevalence increasing across all quartiles. Diabetes prevalence remained unchanged. Median hospital stays decreased (7 to 4.6 days, p<0.01), and median DBT fell significantly (216 to 37 minutes, p<0.01). Both 30-day and 1-year mortality improved (p=0.01), from 13.4% to 6.8% and 19.5% to 12.9%, respectively. Three-year mortality fell from 24.3% to 15.5% (p=0.02). Compared to DBT < 60 minutes, shorter DBT was related to reduced mortality over time after controlling for numerous variables. Conclusion The long-term prognosis for anterior STEMI patients at our center has improved over the previous two decades. DBT decreased with these changes. This study emphasizes the need to optimize door-to-balloon timeframes for anterior STEMI care and prompt intervention. Recommendation Healthcare providers should target anterior STEMI door-to-balloon time reduction based on this study. To improve results in this patient population, smoking, hypertension, and obesity should be addressed. Additional research is needed to improve anterior STEMI patient treatment and care.